The Influence of Problem Based Learning Model on Students' Critical Thinking Skills in Natural and Social Sciences Subject of Class V UPTD SD Negeri 122379 Pematangsiantar - Batubara, Silviantika; Panjaitan, Muktar Bahruddin; Pasaribu, Eva (Jurnal Riset Ilmu Pendidikan, 2025)
The purpose of this study was to determine the effect of the Problem Based Learning model on students' critical thinking skills using an experimental method (pre-experimental design). Data analysis was quantitative/statistical, with the aim of testing the established hypothesis. The research population was in class V of UPTD SD Negeri 122379 Pematangsiantar located on Jl. Sentosa. The sample in this study was taken from one class used as a One Group class so that the sample of this study was all students of class V of UPTD SD Negeri 122379 Pematangsiantar. The data analysis technique used in this study was 27 students. The results of the study showed an increase in students' critical thinking skills, namely with an average posttest of 81.48 while the pretest was 57.22. The effect of the Problem Based Learning model on students' critical thinking skills using the Hake factor with the N-Gain test obtained a value of 0.58 with a moderate category.